Sosialisasi Implementasi UU PLP (Pendidikan dan Layanan Psikologi) dan SIAP-HIMPSI - Yuwono, Susatyo; Zulfa Qatrunnada, Rizqi; Kusuma, Patria Jati (Redtech Putra Benua, 2024)
The socialization and implementation of the UU-PLP and SIAP HIMPSI are carried out with the aim of providing information to all HIMPSI members about the new regulations, which govern ethics and relations with and work under the Psychology graduate flag. Previously, HIMPSI members were governed by the 2010 Code of Ethics for Psychologists. However, this has now been replaced by the regulations in the UU-PLP 2022. Therefore, this socialization and implementation is considered important to be carried out, one of which is through a socialization event at Muhammadiyah University of Surakarta, targeting participants such as HIMPSI members, professionals with a background in psychology, and psychology students from the surrounding Surakarta ex-Karesidenan area.